PENGARUH BRAND IMAGE, INOVASI PRODUK, DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Produk Kosmetik Sariayu di Jabodetabek) - Nada Nabila, (2023)
This research is quantitative research which aims to determine the influence of Brand Image, Product Innovation, and Electronic Word of Mouth on Purchasing Decisions. This research uses primary data with a population of consumers aged at least 17 years who live in Jabodetabek and have purchased or used Sari Ayu cosmetic products. The observation data for this research amounted to 104 respondents. The data analysis method was carried out using Structural Equation Modeling (SEM), which is usually called partial least squares (PLS) as a data analysis method using Smart PLS 3.2.9. The results of hypothesis testing show that (1) Brand Image has a significant effect on Purchasing Decisions, (2) Product Innovation has a significant effect on Purchasing Decisions, (3) Electronic Word of Mouth has no effect and is not significant on Purchasing Decisions.